2011
DOI: 10.1007/s11663-011-9528-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Residual Elements Arsenic, Antimony, and Tin on Surface Hot Shortness

Abstract: Scrap-based electric arc furnace (EAF) steelmaking is limited by a surface cracking problem in the recycled steel products, which is known as surface hot shortness. This problem originates from the excessive amount of copper (Cu) in the steel scrap, which enriches during the oxidation of iron (Fe) and consequently melts and penetrates into the austenite grain boundaries. In this article, the effects of arsenic (As), antimony (Sb), and tin (Sn) on surface hot shortness were investigated. A series of Fe-0.3 wt p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…For example, arsenic reduces the quality of raw materials, affects the extraction of metal, interferes with the purity of the product, and poses serious environmental hazards [1]. Arsenic has an adverse effect on steel; for instance, the surface hot shortness increases, and the reduction of area and impact toughness decrease with the increase of arsenic content in steel [3][4][5][6]. Under the hot rolling or welding conditions, the arsenic in the steel leads to the increase in the content of arsenic at grain boundaries and the expansion of welding cracks [4,[7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…For example, arsenic reduces the quality of raw materials, affects the extraction of metal, interferes with the purity of the product, and poses serious environmental hazards [1]. Arsenic has an adverse effect on steel; for instance, the surface hot shortness increases, and the reduction of area and impact toughness decrease with the increase of arsenic content in steel [3][4][5][6]. Under the hot rolling or welding conditions, the arsenic in the steel leads to the increase in the content of arsenic at grain boundaries and the expansion of welding cracks [4,[7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the impurities are unavoidably accumulated in the steel scraps recycling. Once the impurities concentration exceeding a certain limit, they would considerably affect steel properties such as hot ductility deterioration [1], hot shortness [2].…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10] However, these studies almost focused on the copper content ranging from 0.25 wt% to 1.0 wt% instead of the lower copper content more commonly produced by electric furnaces, even the oxidation behavior and surface hot shortness of steels with the lower content of coexisted copper and arsenic. So far, Yin L. et al 11) has investigated the effect of 0.06 wt%-0.1 wt%As on oxidation behavior of Fe-0.3wt%Cu alloy in the (Received on January 2, 2016; accepted on March 17, 2016) To avoid surface hot shortness of C-Mn steels containing arsenic and copper + arsenic, high temperature oxidation behavior of the steels were systematically investigated. The results showed that the presence of arsenic and copper + arsenic accelerated oxidation degree of C-Mn steel.…”
Section: Introductionmentioning
confidence: 99%